Provoking elite schools' defences: an antistrophon. Issue 4 (3rd July 2020) - Prosser, Howard
ABSTRACT: Elite schools, both private and public, consistently top metrics of success around the world. This article mobilises an antistrophon – turning an argument against itself – to expose elite schools' rhetorical defences. As part of this device, four provocations are offered – knowledge, excellence, merit, values – that coincide with elite schools' identity. These provocations are explored in light of a growing global corpus of scholarship on elite schools that consistently reveals how they reinforce their status and justify social inequality. Implicit to the argument is the idea that non-elite schools and school systems imitate such practices. It concludes by suggesting elite schools' shrewdness in obscuring their unjust exclusivity must be continually illuminated, scrutinised, and challenged if social inequality is to be combatted.